Perencanaan Ulang Tata Letak dalam Pengoptimalan Ruang pada Ritel Sejahtera Mart di Bogor - Angelica Nabilla Ahdy; Chintya Kenisah Gultom; Rhaka Agung Setiawan; Zakwan Zaky Bahara Simbolon (Pusat Riset dan Inovasi Nasional, 2024)
Designing the layout is an important key in ensuring company operations run efficiently in the long term. Several problems have been identified at Sejahtera Mart, especially regarding the layout of frozen food and chillers, as well as shopping baskets that are less efficient. A layout that is not optimal can make it difficult for customers to find the items they need, thereby affecting customer satisfaction. This research uses the Activity Relationship Chart (ARC) method to analyze the relationship between facilities, and Total Closeness Rating (TCR) to evaluate the benefits of a layout that suits the product material flow and the shortest material flow distance that can be achieved. The research results show that the placement of the chiller and shopping basket layout in the layout solution has changed. Based on TCR analysis, the display rack shows the highest score with a TCR of 330, followed by the cashier with a score of 217. This research aims to redesign the layout of the facilities at Sejahtera Mart to be more efficient and effective in placing products and organizing space. It is hoped that these changes will improve sales, customer experience and maximize space use.